Production and use of biochar from buffalo‐weed (Ambrosia trifida L.) for trichloroethylene removal from water. Issue 1 (19th July 2013) - Ahmad, Mahtab; Moon, Deok Hyun; Vithanage, Meththika; Koutsospyros, Agamemnon; Lee, Sang Soo; Yang, Jae E; Lee, Sung Eun; Jeon, Choong; Ok, Yong Sik
Abstract BACKGROUND Ambrosia trifida L. (buffalo‐weed) is a ubiquitous invasive plant species in Korea, causing severe allergy problems to humans and reduction in crop yields. Converting buffalo‐weed biomass to biochar and its use as an adsorbent for the depuration of trichloroethylene (TCE) contaminated water could help resolve two existing environmental issues simultaneously. RESULTS The plant biomass was converted to biochar at 300 °C (BC300) and 700 °C (BC700). The pyrolysis temperature strongly influenced the properties of resulting biochars. The higher temperature resulted in a higher degree of C‐enrichment. The loss of H‐ and O‐containing functional groups shifted the BC700 composition towards a less polar, more aromatic carbon structure evidenced by lower O/C (0.06) and H/C (0.15) values compared with those of BC300 (0.07 and 0.65, respectively). These properties of BC700 further highlighted its greater efficiency of TCE removal (88.47%) from water, compared with that of BC300 (69.07%). The TCE adsorption data was well described by the Hill isotherm model indicating the mechanism of adsorption to be cooperative interaction. Linear correlations between model parameters and biochar properties were also observed. CONCLUSIONS Buffalo‐weed can be converted to value‐added biochar that can be used as an effective adsorbent for the treatment of TCE contaminated groundwater. © 2013 Society of Chemical Industry